2020
DOI: 10.2337/dc20-0660
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Patients With Diabetes and COVID-19 in Association With Glucose-Lowering Medication

Abstract: OBJECTIVEDiabetes is one of the most distinct comorbidities of COVID-19. Here, we describe the clinical characteristics of and outcomes in patients with diabetes in whom COVID-19 has been confirmed or clinically diagnosed (with typical features on lung imaging and symptoms), and their association with glucose-lowering or blood pressure-lowering medications. RESEARCH DESIGN AND METHODSIn this retrospective study involving 904 patients with COVID-19 (136 with diabetes, mostly type 2 diabetes), clinical and labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
215
2
20

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(263 citation statements)
references
References 26 publications
26
215
2
20
Order By: Relevance
“…These results suggest that mechanisms through which type 2 diabetes and cardiovascular disease increase vulnerability to Covid-19 may overlap and are not additive. Although we did not investigate for the impact of cardiovascular disease on Covid-19 progression among inpatients, our data are in line with other studies which did not find independent associations between prior history of cardiovascular events and outcomes among patients with diabetes hospitalized for Covid-19 [18][19][20]. This topic needs, however further investigations, being still debated as contrasting data are reported depending on the chosen outcome [20].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These results suggest that mechanisms through which type 2 diabetes and cardiovascular disease increase vulnerability to Covid-19 may overlap and are not additive. Although we did not investigate for the impact of cardiovascular disease on Covid-19 progression among inpatients, our data are in line with other studies which did not find independent associations between prior history of cardiovascular events and outcomes among patients with diabetes hospitalized for Covid-19 [18][19][20]. This topic needs, however further investigations, being still debated as contrasting data are reported depending on the chosen outcome [20].…”
Section: Discussionsupporting
confidence: 66%
“…According to the prespecified enrolment plan and matching strategy (Supplementary material), 158 controls matched for age and sex with the 79 Covid-19 cases were enrolled. When this analysis was carried out, 9 out of the 79 cases (11.4%) died 20 [12][13][14][15][16][17][18][19][20][21][22][23][24] days after hospitalization, 38 (48.1%) were discharged after 23 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] males, p = 0.92) and body mass index. Cases were less likely ever smokers than controls (22.8% vs 45.6%, p = 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…As for diabetes, previous studies have shown that diabetes can affect the prognosis of patients with viral pneumonia and it should, therefore, be analyzed separately from other comorbid diseases (15). In the univariate analysis performed here and in a previous study by Chen et al (17), diabetes was found to be associated with poor COVID-19 outcome. For this reason, we analyzed data from the diabetes patients separately from those with other comorbid diseases.…”
Section: Discussionmentioning
confidence: 50%
“…An association between diabetes, glycemic control and COVID-19 outcomes has been previously suggested in several studies, mostly coming from China [15,16]. It is important to note, however, that clinical features of patients reported in previous studies were different from ours on several aspects and that adjustment for confounding variables was heterogeneous [8,17]. Finally, different endpoints were considered, going from radiographic findings to ICU admission to in-hospital mortality [7].…”
Section: Discussionmentioning
confidence: 77%